A Novel Trichothecene Metabolite from Myrothecium cinctum 910 and its Biological Activity - Tsyhanenko, K.S.; Pavlychenko, A.K.; Andrienko, O.V.; Savchuk, Ya.I.; Циганенко, К.С.; Павличенко, А.К.; Андрієнко, О.В.; Савчук, Я.І. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Fungi of the Myrothecium genus are well-known producers of macrocyclic trichothecenes, characterized by the acute toxic effect on warm-blooded organisms and fungicidal action against a wide range of fungi. At the same time, as established by us earlier, M. cinctum (current name Striaticonidium cinctum) 910 shows a wide spectrum of antibacterial activity: along with antifungal activity against mycelial, yeast-like and phytopathogenic test-cultures it strongly inhibited the growth of gram-positive test-strains and to lesser extend – the growth of gram-negative and phytopathogenic bacteria. This strain also revealed significant phytotoxic potential suppressing the growth of green algae Chlorella strains. The aim of the work was to isolate, to purify and to obtain in crystalline form the biological active metabolites of M. cinctum 910 and to study their physicochemical characteristics and biological activity. Methods. To obtain biologically active metabolites in the purified crystalline form, the extraction followed by separation by column chromatography and recrystallization was used; physicochemical methods and microbiological tests were used for characterization of their properties. Results. Three substances which showed the wide spectrum of biological activity to indicator test-cultures were obtained in crystalline form: preparation МС910 with high antibiotic activity and preparations from fractions 8/2 and 9 with high antifungal and phytotoxic activities. Taking into account the data of spectroscopy in the UV-range of spectrum, of spectrums of antibiotic activity and of qualitative reaction with 4-(4-nitrobenzyl)pyridine, it can be concluded that active fractions  8/2 and  9 contain macrocyclic trichothecenes whereas the metabolite МС910 (which is proved by data of IR-spectroscopy) belongs to simple trichothecenes – substances like to macrocyclic trichothecenes but without macrocyclic fragment in their structure. Conclusions. Antibiotic properties of M. cinctum 910 are due to the complex of biological active metabolites with different biological and physicochemical properties. In view on the biological activity of MC910, it can be argued that it has atypical for trichothecenes, including macrocyclc trichothecenes, antibacterial properties as well as it is non-toxic and does not reveal dermatocidal activity in studied concentrations. Therefore, we assume that MC910 is new, not described earlier metabolite of trichothecene nature, which needs further studies. At the same time, active metabolites from fractions 8/2 and 9 are represented by macrocyclic trichothecenes, which is also indicated by the spectra of their biological activity.